1993
DOI: 10.3168/jds.s0022-0302(93)77421-4
|View full text |Cite
|
Sign up to set email alerts
|

Separation and Characterization of the C-Terminal Half Molecule of Bovine Lactoferrin

Abstract: The C-terminal half molecule (C lobe) of bovine lactoferrin was isolated by mild tryptic hydrolysis of lactoferrin followed by gel filtration and ion-exchange chromatography. The identity of the fragment was established by determining its N-terminal and C-terminal amino acid sequences and comparing them with the amino acid sequence of intact lactoferrin. The isoelectric point of the C lobe ranged between pH 6.2 and 6.5 as measured by isoelectric focusing on polyacrylamide gels. The circular dichroic spectrum i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 22 publications
3
19
1
Order By: Relevance
“…The nonequivalence of iron binding to the amino-and carboxyl-terminal lobes of lactoferrin has been reported previously (36,41,42). Studies using a cloned NH 2 -terminal fragment of human lactoferrin (41) and a proteolytically derived COOHterminal fragment from bovine lactoferrin (42) have shown a similar disparity in pH dependence of iron binding as reported in this study.…”
Section: Discussionsupporting
confidence: 87%
“…The nonequivalence of iron binding to the amino-and carboxyl-terminal lobes of lactoferrin has been reported previously (36,41,42). Studies using a cloned NH 2 -terminal fragment of human lactoferrin (41) and a proteolytically derived COOHterminal fragment from bovine lactoferrin (42) have shown a similar disparity in pH dependence of iron binding as reported in this study.…”
Section: Discussionsupporting
confidence: 87%
“…on immune cells will probably exist in cats and may act as an immunomodurator in feline immune system. In present study, the binding of bLF to ConA could partly explain its inhibitory effect on the ConA-induced cytokine expressions [29]. However, our results showed that bLF inhibited expression of ConA-induced IFN-γ and IL-2 regardless of the time of addition of bLF to the cells.…”
Section: Cycle Numbercontrasting
confidence: 55%
“…Apoprotein residual iron charge was checked by absorption spectroscopy, where the ratio of the absorbance at 465 nm was 0.9% that at 280 nm, indicating a lack of iron in the protein (Ainscough, 1980;Chung and Raymond, 1993). Protein purity was confirmed by the absence of an absorbance peak at 412 nm, which is the indicator of a haemopexin impurity (Shimazaki et al, 1993). Purity and iron load were further checked by uredpol yacrylamide gel electrophoresis according to Makey and Seal (1976).…”
Section: Methodsmentioning
confidence: 99%